2017
DOI: 10.1177/1179555717692545
|View full text |Cite
|
Sign up to set email alerts
|

Hanging Fatalities in Central Bangkok, Thailand: A 13-Year Retrospective Study

Abstract: Hanging is violent asphyxial death. The objective of this study is to assess the data of hanging cases. A descriptive-retrospective study was conducted. We studied 244 hanging cases autopsied in Forensic Division, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand, between January 2001 and December 2013. The study included 197 men (80.7%) and 47 women (19.2%). Their age ranged from 14 to 93 years. Most of these cases were incomplete hanging (83.6%). Feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 36 publications
5
8
0
10
Order By: Relevance
“…This finding agrees with published studies and case reports [1,2,13–20,22–73]. According to a sample of published data summarized in Table 8, full suspension in hanging suicides appears to be more prevalent than partial suspension in eastern cultures [48–64]. Most suicides in the current study, which occurred in North America, were found partially suspended by their neck ligatures, with their feet or knees touching the ground or nearby furniture.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding agrees with published studies and case reports [1,2,13–20,22–73]. According to a sample of published data summarized in Table 8, full suspension in hanging suicides appears to be more prevalent than partial suspension in eastern cultures [48–64]. Most suicides in the current study, which occurred in North America, were found partially suspended by their neck ligatures, with their feet or knees touching the ground or nearby furniture.…”
Section: Discussionsupporting
confidence: 91%
“…A relatively consistent detail observed in this study was the tension of neck ligatures in the cases analyzed, which agrees with the forensic literature [22–70]. Knotted homicide strangulation ligatures were typically tighter than suicide ligatures used for hanging.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations